Effect of aerobic training on inter-arm coordination in highly trained swimmers - Schnitzler, C.; Seifert, L.; Chollet, D.; Toussaint, H. (Human Movement Science, 2013)
The effect of three months of aerobic training on spatio-temporal and coordination parameters was examined during a swim trial at maximal aerobic speed. Nine male swimmers swam a 400-m front crawl at maximal speed twice: in trial 1, after summer break, and trial 2, after three months of aerobic training. Video analysis determined the stroke (swimming speed, stroke length, and stroke rate) and coordination (Index of Coordination and propulsive phase duration) parameters for every 50-m segment. All swimmers significantly increased their swimming speed after training. For all swimmers except one, stroke length increased and stroke rate remained constant, whereas the Index of Coordination and the propulsive phase duration decreased (p < .05). This study suggests that aerobic training developed a greater force impulse in the swimmers during the propulsive phases, which allowed them to take advantage of longer non-propulsive phases. In this case, catch-up coordination, if associated with greater stroke length, can be an efficient coordination mode that reflects optimal drag/propulsion adaptation. This finding thus provides new insight into swimmers` adaptations to the middle-distance event.